2017
DOI: 10.1515/gospo-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of assignment of Mineral Deposits of Public Importance proposed by MINATURA2020 Project and results of its pilot testing in the Dolnośląskie Province (SW Poland)

Abstract: MINATUR A2020 project’s aim is to develop a concept and multi-dimensional methodology of assignment and - in a consequence - of safeguarding the Mineral Deposits of Public Importance (MDoPI) at European (EU), country (CL ) and regional/local level (RL ), in order to ensure their optimal use for future needs of the society. MDoPI assignment methodology proposed within MINATUR A2020 project, was tested within a few EU regions, including Dolnośląskie Province in Poland, where undeveloped deposits were verified. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, the highest (Eu) level is not the case when we analyze the rock minerals deposits. Kot-niewiadomska et al (2017) and Galos et al (2018) presented a comprehensive description of the methodology proposed within the project. therefore, in this paper, we present only major principles of valorization in relation to undeveloped deposits with recognized mineral resources.…”
Section: Methodology Of Valorization Proposed Withinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the highest (Eu) level is not the case when we analyze the rock minerals deposits. Kot-niewiadomska et al (2017) and Galos et al (2018) presented a comprehensive description of the methodology proposed within the project. therefore, in this paper, we present only major principles of valorization in relation to undeveloped deposits with recognized mineral resources.…”
Section: Methodology Of Valorization Proposed Withinmentioning
confidence: 99%
“…the methodology developed within the MInAtuRA 2020 project was tested in some european countries. in Poland, analyses were limited to the dolnośląskie Province territory and included undeveloped deposits belonging to a selected group of raw materials (magmatic and metamorphic crushed and dimension stone, feldspar raw materials, kaolin, and glass sand (Kot-niewiadomska et al 2017). Deposits of sand and gravel have not been analyzed so far, as they have not been taken into consideration in testing procedures within the MInAtuRA 2020 project.…”
Section: Methodology Of Valorization Proposed Withinmentioning
confidence: 99%
“…However, the need to assign specific areas to mining activities and to reconcile active or latent conflicts with other land uses is not free of controversy, being additionally of problematical implementation. Different approaches have been recently proposed to deal with these issues [48][49][50]. In this study, we will use the multi-criteria methodology reported in [48], which relies on the concept of mineral resources of public importance (MRoPI).…”
Section: Multi-criteria Methodology For Delimit Tungsten Resources Of Public Importancementioning
confidence: 99%
“…In Poland, the methodology of ranking and assessment of deposits has been repeatedly applied to various types of minerals (e.g., [91][92][93][94][95][96][97][98][99][100][101]). As a result of such extensive work, deposits were selected which-based on various criteria, but basically in view of the size of resources and quality of the minerals-seem to be the most attractive and valuable.…”
Section: Indications On the Safeguarding Of Deposits For The Production Of Selected Key Mineralsmentioning
confidence: 99%
“…Testing of the evaluation for selected rock mineral deposits in Poland made it possible to indicate six rock mineral deposits which should be subject to safeguarding, including five for which the safeguarding should be considered at the national level. For kaolin two such deposits were selected and the remaining eight would be considered for safeguarding at the regional level [101].…”
Section: Indications On the Safeguarding Of Deposits For The Production Of Selected Key Mineralsmentioning
confidence: 99%